Le changement climatique et ses impacts sur l’agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Le changement climatique et ses impacts sur l’agriculture au Sénégal